Correction to: The low-copy nuclear gene Agt1 as a novel DNA barcoding marker for Bromeliaceae - Bratzel, Fabian; Heller, Sascha; Cyrannek, Nadine; Paule, Juraj; Leme, Elton M. C.; Loreth, Anna; Nowotny, Annika; Kiefer, Markus; Till, Walter; Barfuss, Michael H. J.; Lexer, Christian; Koch, Marcus; et al. (BMC plant biology, 2020)
An amendment to this paper has been published and can be accessed via the original article.